A curious new genus of Keroplatini (Diptera: Keroplatidae) from Guatemala - Fitzgerald, Scott J. (Zootaxa, 2019)
Amerikeroplatus dimorphicus n. gen. et n. sp. is described from Guatemala and compared with the similar Keroplatini genera Pseudochetoneura Ševčík and Asiokeroplatus Ševčík. The new genus is distinctive because it lacks the typical fusion of M and R (radiomedial fusion, RS+M) which is found in all but a few species-poor, and apparently unrelated, genera of keroplatids. Also unusual is the absence of vein R2+3 and the strong sexual dimorphism in the thorax; males are dark brown and females bright orange.